Comparison of marginal and internal fit of press-on-metal and conventional ceramic systems for three- and four-unit implant-supported partial fixed dental prostheses: An in vitro study - YILDIZ, COŞKUN; ÖZKAN, YASEMİN (MOSBY-ELSEVIER, 2015)
Statement of problem. Adaptation is an important factor in the long-term clinical success of implant supported ceramic restorations. Ceramic firings may affect the adaptation of the restoration. Purpose. The purpose of this study was to compare the marginal and internal adaptation of 3 different restorative materials and the effect of veneering/pressing on the material used for 3- and 4-unit implant supported fixed dental prostheses. Material and methods. One mandibular epoxy cast was prepared for 3-unit restorations and one for 4-unit restorations. Impressions of the casts were made and 60 stone die casts (30 3-unit, 30 4-unit) produced. The casts were divided into 3 subgroups: group MCR, conventional metal ceramic restorations; group POM, press-on-metal restorations; group ZIR, computer-aided design/computer-aided manufacturing CAD/CAM) zirconia restorations. A replica technique was used to examine the marginal and internal gap values. A total of 2400 measurements were made by making 40 measurements of each restoration. The data were evaluated statistically using analysis of variance and the least significant difference post hoc test (alpha=.05). Results. The lowest marginal gaps were found in group POM (81.58 mu m) and the highest in group MCR (103.82 mu m). The differences in marginal adaptation measurements were found to be statistically significant. The highest values for internal adaptation were found at the occlusal surface in all groups. Conclusions. Although veneering metal ceramic restorations increased the misfit of the restoration, the marginal discrepancy of the materials (81 to 120 mu m) can be considered clinically acceptable.
Keywords: TITANIUM COPINGS; PARTIAL DENTURES; CLINICAL FIT; CROWNS; ADAPTATION; SUPERSTRUCTURE; RESTORATIONS; ACCURACY